A Study of Face-to-Face and Online Teaching Philosophies in Canada and Australia - Stacey, Elizabeth; Wiesenberg, Faye (International Journal of E-Learning & Distance Education / Revue internationale du e-learning et la formation à distance, 2007)
The perspectives of instructors who teach both online and face-to-face in a higher education context have been compared in this study. The differences and similarities between their approaches, and the influences each modality has on the other have been explored, as well as possible differences in organizational cultures between the groups who were based in Canada and Australia. The trend to blended learning in higher education was an important outcome of the study Les points de vue des formateurs qui enseignent en ligne et en face à face dans un contexte universitaire ont été comparés dans cette étude. Les différences et les similarités entre les approches, et les influences que chaque modalité a sur l’autre ont été examinées, en même temps que les différences de culture organisationnelle entre les groupes situés au Canada et en Australie. L’identification de la tendance vers l’apprentissage mixte (blended learning) aux études universitaires est un résultat significatif de l’étude.